KERAGAMAN DAN KEKERABATAN GENETIK GARCINIA BERDASARKAN KANDUNGAN SENYAWA BIOAKTIF DAN AKTIVITAS BIOLOGISNYA: KAJIAN IN SILICO - Dindin Hidayatul Mursyidin; Fajar Nurrahman Maulana (BERITA BIOLOGI, 2020)
Garcinia, belongs to the genus Guttiferae, is a very prospective plant for development. Because of apomixis, however, this plant has a narrow genetic diversity. This study aims to determine the genetic diversity and relationships of Garcinia based on the content of bioactive compounds and its biological activities, using in silico approach. A total of 64 Garcinia species were analyzed by a multivariate method using the MVSP ver. 3.1 software. The results showed that based on these characters, Garcinia had a low (narrow) genetic diversity, with a Shannon index of 0.28. However, the xanthone, antifungal activity, and leaf organ are the three of Garcinia characters with a high (wide) genetic diversity. The PCA revealed that these characters are contributed positively to this genetic diversity. The UPGMA analysis also revealed that this germplasm is divide into six main clusters, where the fifth is the largest (53 species). The farthest relationship is shown by G. hanburyi and G. cylindrocarpa, as well as G. bancana and G. excavata, at a coefficient of 0.54. In this case, G. mangostana, the most popular species of Garcinia, has the closest relationship with G. wightii at a coefficient of 0.87, and fartest to G. cylindrocarpa. This information might be valuable in supporting the preservation and breeding programs of Garcinia in Indonesia, particularly for parental selection in the development of superior cultivars.